(untitled) (Palestine Issues on Indonesian Society, 2024)
This paper examines the role of Indonesian cultural figures in advocating for Palestinian rights on the international stage. Focusing on artists, musicians, filmmakers, and intellectuals, this study analyzes how Indonesia’s cultural diplomacy has been utilized to raise awareness about the Palestinian issue globally. The paper highlights how Indonesian cultural expressions—through art exhibitions, performances, and public statements—serve as a platform for solidarity, as well as tools for framing the Palestinian cause within a broader discourse of justice, human rights, and resistance. It explores the alignment of Indonesian cultural diplomacy with its political and religious identity, particularly in the context of Indonesia’s position as the world’s largest Muslim-majority country. The paper also considers the influence of Indonesian cultural figures in global civil society networks, especially in shaping narratives about Palestine within cultural spaces such as the United Nations and other international platforms. By analyzing the strategies and impact of these figures, this study offers insights into the intersection of culture, diplomacy, and international advocacy.